Seed Macro- And Micro-Morphology of Some Species Of Kickxia Dumort, Scrophularia L. And Plantago L. From Saudi Arabia (Bangladesh Journal of Plant Taxonomy, 2021)
The seed macro- and micro-morphological characters of 13 species belonging to three genera; Kickxia Dumort, Scrophularia L. and Plantago L., collected from different localities of Saudi Arabia, were studied using a Stereomicroscope and Scanning Electron Microscope for evaluating their taxonomic relationships. Three macro-morphological characters of seeds were shape, size, and color while three diagnostic micromorphological characters were seed coat sculpture, the anticlinal and periclinal wall., The seed shape seems to be specific in Plantago L. (peltate, angled) than the two other genera while the color and seed size show little importance. The Plantago L. has a specific rugose sculpture while the other two genera have either tuberculate or alveolate. So Plantago L. was possessed no affinities to Kickxia Dumor or Scrophularia L.. This observation gives extra support to the earlier taxonomic views that suggested the retention of two genera in the traditional family Scrophulariaceae and maintaining Plantago L. in a separate monogeneric family Plantaginaceae Detailed analysis of seed characters of more species is needed to clarify the systematic relationships between the three genera. A key to the identification of studied species based on seed micro- and macro-morphological characters is provide.Bangladesh J. Plant Taxon. 28(2): 385-393, 2021 (December)